PSYCHOLOGICAL STRESS ON NURSE PERFORMANCE IN PROVIDING NURSING CARE DURING THE COVID-19 PANDEMIC - Meirizal Ari Putra (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2021)
Objectives: This study examines the psychological stress experienced by nurses, explores the psychological stress on nurses' performance in providing nursing care in hospitals during the COVID-19 pandemic. Methods: In this study using a qualitative design with an analytical strategy using in-depth interviews, the subjects used were nurses who worked in two Yogyakarta hospitals, the sampling technique used consecutive sampling, which was then carried out qualitative analysis. Results: The research has two themes. First, the psychological stress experienced at the beginning of the pandemic with four sub-themes, namely; 1) fatigue and PPE problems during the pandemic; 2) fear of infection; 3) anxiety caused by community stigmatization; 4) concern for family health. Second, coping and self-care with three sub-themes, namely; 1) awareness and vigilance on duty; 2) spiritual support; 3) support for facilities and infrastructure. Conclusion: Research provides in-depth knowledge of the stress experienced by nurses in the COVID-19 pandemic situation and can provide advice to hospital management in ensuring the health and safety of nurses in the hospital. Recommendation: Hospitals can improve the Standard Operating Procedures, mental support, support for personal protective equipment to protect nurses to minimize the negative impact in nurses in providing nursing care in a pandemic situation.